Transcriptomic analysis reveals numerous diverse protein kinases and transcription factors involved in desiccation tolerance in the resurrection plant Myrothamnus flabellifolia. (22nd July 2015) - Ma, Chao; Wang, Hong; Macnish, Andrew J; Estrada-Melo, Alejandro C; Lin, Jing; Chang, Youhong; Reid, Michael S; Jiang, Cai-Zhong
Abstract: The woody resurrection plant Myrothamnus flabellifolia has remarkable tolerance to desiccation. Pyro-sequencing technology permitted us to analyze the transcriptome of M. flabellifolia during both dehydration and rehydration. We identified a total of 8287 and 8542 differentially transcribed genes during dehydration and rehydration treatments respectively. Approximately 295 transcription factors (TFs) and 484 protein kinases (PKs) were up- or down-regulated in response to desiccation stress. Among these, the transcript levels of 53 TFs and 91 PKs increased rapidly and peaked early during dehydration. These regulators transduce signal cascades of molecular pathways, including the up-regulation of ABA-dependent and independent drought stress pathways and the activation of protective mechanisms for coping with oxidative damage. Antioxidant systems are up-regulated, and the photosynthetic system is modified to reduce ROS generation. Secondary metabolism may participate in the desiccation tolerance of M. flabellifolia as indicated by increases in transcript abundance of genes involved in isopentenyl diphosphate biosynthesis. Up-regulation of genes encoding late embryogenesis abundant proteins and sucrose phosphate synthase is also associated with increased tolerance to desiccation. During rehydration, the transcriptome is also enriched in transcripts of genes encoding TFs and PKs, as well as genes involved in photosynthesis, and protein synthesis. The data reported here contribute comprehensive insights into the molecular mechanisms of desiccation tolerance in M. flabellifolia . Abstract : Drought tolerance: Molecular mechanisms in a resurrection plant Molecular responses to dehydration in a desert plant may suggest targets for engineering drought-tolerant crops. Plants able to withstand extreme dehydration, such as Myrothamnus flabellifolia, are known as 'resurrection plants.' The mechanisms by which they survive and revive after drought are highly relevant to plant breeding, but are still largely unknown in M.flabellifolia . An international team led by Cai-Zhong Jiang, United States Department of Agriculture, has identified over 8, 000 genes activated on dehydration in M.flabellifolia, and another 8, 500 activated on rehydration. They focused on genes coding for transcription factors, which control when other genes are switched on, and signalling molecules called protein kinases. They found that 484 protein kinases were activated on dehydration, more than twice as many as in non-resurrection plants. These regulatory signals control a range of genes with protective effects.